Ejecución presupuestaria de gastos del Gobierno Autónomo Descentralizado Municipal del Cantón Baba en el período 2022. - Aguirre Franco, Nicole Estefanya (2023)
This study originated from concerns about the management of public resources in the Autonomous Decentralized Government (GAD) of Ricaurte Parish during the year 2021. The problem statement focused on the need to assess and improve internal control processes in accounting procedures to ensure efficiency and transparency in the administration of these resources. The justification for this research lay in the importance of strengthening accountability in local government management, ensuring the proper use of public funds. The general objective was to examine internal control processes in the accounting procedures of the Parish GAD of Ricaurte in the year 2021, through the review of the institution's records and accounting documents as the primary methodology. The results of this research highlighted significant challenges in budget compliance and provided crucial recommendations to enhance the evaluation of internal control policies and increase accuracy in accounting. In summary, this study serves as an essential tool for informed decision-making and driving continuous improvements in the management of local public resources in the Parish GAD of Ricaurte, thereby contributing to the well-being of the community.